2023
DOI: 10.1080/20008066.2023.2187187
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to post-traumatic growth in Korean female cancer patients: the mediation effects of coping strategies and resilience

Abstract: Background: Cancer is a life-threatening disease in Korean women. Female cancer patients in Korea have reported poor physical functioning and psychological distress after diagnosis. However, some patients experience post-traumatic growth (PTG), which includes positive feelings and changes. Objective: The main purpose of this study was to examine the relationships between PTG and its associated factors in Korean female cancer patients to understand how female cancer patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
(62 reference statements)
0
0
0
Order By: Relevance
“…In addition, Boskailo et al did not find a statistically significant relationship between psychological resilience and quality of life in patients diagnosed with breast cancer [35]. In a study, psychological resilience was associated with post-traumatic growth [36]. Michalczyk et al found a positive relationship between psychological resilience and post-traumatic growth in women diagnosed with breast cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Boskailo et al did not find a statistically significant relationship between psychological resilience and quality of life in patients diagnosed with breast cancer [35]. In a study, psychological resilience was associated with post-traumatic growth [36]. Michalczyk et al found a positive relationship between psychological resilience and post-traumatic growth in women diagnosed with breast cancer [37].…”
Section: Discussionmentioning
confidence: 99%